Post-phacoemulsification examination of intraocular pathologies that could not bedetected by fundus biomicroscopy or OCT in eyes with dense cataract: trying to avoid intra- and post-operative complications - Sule Gokcek Gurturk Icoz; Sevde Akcay Usta; Mehmet Icoz (Photodiagnosis and Photodynamic Therapy)
Purpose: : To investigate postoperative intraocular pathologies in eyes with dense cataracts that preclude fundus evaluation. Design: :Retrospective study. Methods: : This study was conducted on 88 eyes from 88 patients.All participants underwent uncomplicated phacoemulsification and intraocular lens implantation due to dense cataracts that prevented fundus evaluation in biomicroscopic dilated fundus examination. In the postoperative first-month follow-up, intraocular pathologies were assessed via dilated biomicroscopic fundus examination, color fundus photography, and optical coherence tomography.Potential risk factors were identified using univariate and multivariate regression analyses. Results: : The mean age of the patients was 69 ± 11 (range:28–92) years, with 49 being female. Intraocular pathologies were detected in 33 patients (37 %).The most frequently observed pathologies were diabetic retinopathy (n = 11, 13 %), followed by age-related macular degeneration (n = 7, 8 %), epiretinal membrane (n = 6, 7 %), full-thickness or lamellar macular holes (n = 3, 3 %), photoreceptor damage (n = 2, 2 %), glaucomatous changes (n = 2, 2 %), myopic degeneration (n = 1, 1 %), and vitreomacular traction (n = 1, 1 %).Both univariate and multivariate regression analyses revealed diabetes mellitus and the presence of pathology in the fellow eye as significant risk factors for postoperative intraocular pathologies in patients with dense cataracts (p < 0.05 and p < 0.001,respectively). Conclusion: : A considerable proportion of intraocular pathologies were detected postoperatively in eyes with dense cataracts.Diabetes mellitus and the presence of pathology in the fellow eye were found to be significant risk factors for postoperative intraocular pathologies in both univariate and multivariate regression analyses.These findings provide valuable evidence for clinicians and patients regarding postoperative intraocular pathologies in eyes with mature cataracts.